STRATEGI KOMUNIKASI PEMASARAN TERPADU MANGSI COFFEE DALAM MEMPERKENALKAN KOPI ARABIKA BALI SEBAGAI PRODUK UNGGULAN LOKAL - Yoga Sumantara, I Wayan; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
Mangsi Coffee is a brand of local origin of Bali since 2004 that produces Arabica Coffee comes from the region of Kintamani. Mangsi Coffee have innovation that is mixed with spices derived from nature, so it has the characteristic as well as competitive power as local products. The purpose of this research is to know the marketing communication strategy used Mangsi Coffee in introducing Balinese Coffee Arabica to local people. This research is using descriptive qualitative approach . The informants were selected by using purposive . The data were obtained by doing interview, direct observation and documentation study. The technique of analyzing the data that used in this research through several steps that was data reduction, data display and conclusion drawing . The result of this research shows the strategy integrated marketing communication ( IMC) conducted by Mangsi Coffee in each and every products have some difference in strategy, 5S Mangsi Original product in aluminium sachet separate sugar was introduced to local people with strategies, personal selling, sales promotion, advertising, direct selling, public relation, and interactive marketing. While eleven other Mangsi product packaged in paper box only use the strategy of advertising, direct selling, public relation, and interactive marketing. Mangsi Coffee in introducing Bali Arabica Coffee as a local superior product also uses the concept word of mouth, which is considered as the strongest and trusted promotion concept.   Keywords : Mangsi Coffee, Arabica Coffee Bali, Integrated Marketing Communication Strategy, IMC